تحليل صعوبة تعلم اللغة العربية للطلاب الجامعي في كلية التربية بجامعة الاسلامية "علووية" بمجوكرتو - Bastian, Achmad Fandi; Munir, Muhammad Mubasyir; Kouyate, Sekou (Al-Fakkaar, 2024)
Learning is a process or endeavor undertaken by each individual to bring about a change in behavior, learning a subject was difficult and problematic, as well as learning Arabic as a second language is also difficult. The difficulty in learning Arabic as a second language increased for university students who did not enroll in Arabic. This article seeks to expose the learning difficulty of undergraduate students graduating from non-religious schools and the efforts the university has made to overcome those difficulties. The research used the qualitative descriptive approach especially the case study, Data on the difficulties of learning Arabic was collected in an interview with the lecturer and some students, and the progress of teaching and learning was observed, and documents were collected on the factors affecting the difficulty of learning Arabic.. The results from this research seem to mean that the learning difficulty of students seems focused on the two factors, they are the internal factor means the lack of motivation in learning the Arabic language different from their professional goal and the external factor is the boring progress of education and the lack of a book matching the level of their linguistic and cultural. The efforts made by the university are to guide the teacher to encourage students on the importance of the Arabic language and avoid familiarity with teaching grammar, and then write a book corresponding to their linguistic and cultural level.